Management of Islamic Boarding Schools and the Role of Islamic Boarding School Residents (Case Study at the Nurul Anwar Islamic Boarding School, Karduluk Village, Pragaan District, Sumenep Regency, 2026) - Hafi Hafi; Ghozi Mubarok (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Madrasah Diniyah Takmiliyah plays a strategic role in shaping the character and religious understanding of students (students). The sustainability and quality of Madrasah Diniyah implementation are greatly influenced by the ability of the institution's management to manage the roles of all members of the Madrasah community, including the principal, teachers, guardians, and the community. This study aims to describe and analyze Madrasah Diniyah management in managing the roles of members of the Madrasah community at Madrasah Diniyah Takmiliyah Nurul Anwar Karduluk, Sumenep Regency. This research used a qualitative approach with a case study approach. Data collection techniques included observation, interviews, and documentation. Research subjects included the Madrasah principal, teachers, guardians, and other relevant parties. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity tested using source and technique triangulation. The results indicate that Madrasah Diniyah management in managing the roles of members of the Madrasah community is implemented through four management functions: planning, organizing, implementing, and monitoring. Planning is carried out in a participatory manner, involving members of the Madrasah community. The organization of roles is tailored to the competencies and conditions of each madrasah member. Role implementation is quite effective, despite limited facilities and resources. Internal supervision is conducted by the madrasah principal through evaluation of learning activities and madrasah programs. This study concludes that participatory management contributes positively to the sustainability and effectiveness of madrasah diniyah management.